Comparison of the Shake Weight® modality exercises when compared to traditional dumbbells - Glenn, J. M.; Cook, I.; Di Brezzo, R.; Gray, M.; Vincenzo, J. L. (Journal of Sports Science & Medicine, 2012)
Individuals are continuously looking for faster, more efficient methods with which to develop physical fitness. This has led to the development of products and programs marketed towards increasing physical fitness in minimal time. The Shake Weight® (SW) has been advertised to increase muscular strength among other factors in less time than traditional weightlifting. The purpose of this study was to compare the electromyographic (EMG) muscle activity of the SW to a traditional dumbbell (DB) performing the same exercises. Twelve men (22.9 ± 1.6 years) and 13 women (23.0 ± 1.9 years) volunteered to participate in this study. Subjects performed the chest shake (CS), biceps shake (BS), and triceps shake (TS) using the SW and DW. Maximal voluntary isometric contractions (MVIC) were exhibited for all muscles. EMG activity was recorded for the pectoralis major (PM), triceps brachii (TB), biceps brachii (BB), anterior deltoid (AD), trapezius (TR), and rectus abdominus (RA) and compared to detect differences between modalities. EMG activity for each muscle group was reported as a percentage of each subject's individual MVIC. A repeated measures ANOVA revealed no significant differences between the SW and DB modalities during each exercise for all muscles except the BB (p < 0.05). During the CS exercise muscle activity was significantly greater for DB in the BB muscle when compared to the SW mode (50.8 ± 28.9%; 35.8 ± 30.8%). The SW did not have any advantage over the DB for any exercise, nor for any muscle group. Further, no muscle group during any of the SW trials exhibited an MVIC over 60%, the level necessary to increase muscular strength.